Platelet Function in Aging - Le Blanc, Jessica; Lordkipanidzé, Marie (Frontiers in Cardiovascular Medicine, 2019)
Aging is associated with an increased incidence of cardiovascular disease and thrombosis. Platelets play a major role in maintaining hemostasis and in thrombus formation, making them a key player in thrombotic disorders. Whereas it is well known that platelet aggregability is increased in vascular diseases, the contribution of age-related changes in platelet biology to cardiovascular risk is not well understood. Several lines of evidence support that platelets from older subjects differ in their function and structure, making their platelets more prone to activation and less sensitive to inhibition. These age-related changes could lead to platelet hyperactivity and to the development of a prothrombotic state in advanced age. This review will focus on platelet biochemical modifications during aging and on the mechanisms by which these alterations could lead to thrombotic disease.